The Concept Of Deadlines In Criminal And Civil Procedure Law, Their Legal Basis And Differences (Eurasian Journal of Humanities and Social Sciences, 2024)
In this article, the concept of “deadlines in criminal and civil procedural law”, their legal basis and differences are solved, the procedure for calculating procedural deadlines,the calculation of deadlines when using procedural coercion measures, the consequences of missed deadlines ,suspension of deadlines,postponement, restoration and preparation of civil and criminal cases for trial.